X-Men. Dark Phoenix [videorecording (Blu-Ray)] - Kinberg, Simon; McAvoy, James, 1979-; Fassbender, Michael, 1977-; Lawrence, Jennifer, 1990-; Hoult, Nicholas, 1989-; Turner, Sophie, 1996-; Sheridan, Tye, 1996-; Shipp, Alexandra; Peters, Evan, 1987-; Smit-McPhee, Kodi; Chastain, Jessica, 1977-; Zimmer, Hans; et al. (Twentieth Century Fox Home Entertainment, 2019)
The story of one of the X-Men's most beloved characters, Jean Grey, as she evolves into her iconic alter ego. During a life-threatening rescue mission in space, Jean is hit by a cosmic force that transforms her into one of the most powerful mutants of all. Wrestling with this increasingly unstable power as well as her own personal demons, Jean spirals out of control, tearing the X-Men family apart and threatening to destroy the very fabric of our planet.